2016
DOI: 10.1590/0103-9016-2014-0323
|View full text |Cite
|
Sign up to set email alerts
|

Genome selection in fruit breeding: application to table grapes

Abstract: Genomic selection (GS) has recently been proposed as a new selection strategy which represents an innovative paradigm in crop improvement, now widely adopted in animal breeding. Genomic selection relies on phenotyping and high-density genotyping of a sufficiently large and representative sample of the target breeding population, so that the majority of loci that regulate a quantitative trait are in linkage disequilibrium with one or more molecular markers and can thus be captured by selection. In this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
(28 reference statements)
0
23
0
1
Order By: Relevance
“…GWS could explain a greater proportion of the observed variance in traits compared with methods based on the identification of individual QTL. This was observed by Viana et al (2016) who compared MAS and genomic selection in a grape breeding population consisting of 143 individuals obtained from a cross between (Vitis rupestris x Vitis arizonica/girdiana) x Vitis vinifera. The efficiency of genomic selection was 1.7 to 11.6-fold higher than that obtained by traditional QTL analysis.…”
Section: Genetics and Molecular Research 15 (4): Gmr15048863mentioning
confidence: 95%
See 1 more Smart Citation
“…GWS could explain a greater proportion of the observed variance in traits compared with methods based on the identification of individual QTL. This was observed by Viana et al (2016) who compared MAS and genomic selection in a grape breeding population consisting of 143 individuals obtained from a cross between (Vitis rupestris x Vitis arizonica/girdiana) x Vitis vinifera. The efficiency of genomic selection was 1.7 to 11.6-fold higher than that obtained by traditional QTL analysis.…”
Section: Genetics and Molecular Research 15 (4): Gmr15048863mentioning
confidence: 95%
“…GWS has rarely been applied to fruit trees, being restricted to apples (Kumar et al, 2012), pears (Iwata et al, 2013), and grapes (Viana et al, 2016). To our knowledge, the present study represents the first attempt to investigate the feasibility of genomic selection in Citrus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the TCR method provided lower accuracy than the G-BLUP and BLASSO methods did, with the BLASSO method standing out in terms of prediction accuracy. In GWS studies for genetic improvement of table grapes, Viana et al (2016a) also reported the superiority of the BLAS-SO method over the ridge regression BLUP method (reparametrization of G-BLUP method) for its efficiency in predicting additive genomic values. ), accuracy (r âa ), and bias (b yâ ), with respective standard deviations, of the additive genomic values estimated by the triple categorical regression (TCR), genomic best linear unbiased predictor (G-BLUP), and Bayesian least absolute shrinkage and selection operator (BLASSO) methods, considering the additive-dominance model on simulated data.…”
Section: Comparison Of the Methodsmentioning
confidence: 99%
“…No Brasil, esta técnica começou a ser aplicada recentemente com sucesso em culturas anuais e perenes (CASTRO et al, 2016;LIMA et al, 2019;RESENDE et al, 2012a;VIANA et al, 2016). Em espécies forrageiras, apesar do uso da pastagem como principal componente das dietas de ruminantes, poucos estudos nacionais trazem tal abordagem, apontando, porém, para seu grande potencial (PEREIRA et al, 2018).…”
Section: Introductionunclassified